Pengaruh Pendidikan Kewirausahaan Terhadap Kreativitas Dan Inovasi Dalam Berwirausaha - Aisyah Putri Rambe; Sarah Nabila; Putri Aulia; Mansur Keling (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This research aims to determine the influence of education on creativity and innovation in entrepreneurship. Entrepreneurship education can arouse the spirit of entrepreneurship. An entrepreneur requires tenacity and skills in running a business. Mastering, understanding and applying one's abilities in running an entrepreneur cannot be separated from the ability to understand entrepreneurial knowledge. Entrepreneurship education is a process of motivating students to recognize the environment and open their own business (entrepreneurship), create different values by devoting the necessary time and effort, also bear financial risks, bear the accompanying psychological and social impacts, and receive monetary rewards. . Entrepreneurship education has a big influence on entrepreneurial motivation, being motivated to become an entrepreneur, being able to create your own business activities, building attitudes, mentality and character.